2007
DOI: 10.1073/pnas.0609923104
|View full text |Cite
|
Sign up to set email alerts
|

Mouse oocytes within germ cell cysts and primordial follicles contain a Balbiani body

Abstract: The Balbiani body or mitochondrial cloud is a large distinctive organelle aggregate found in developing oocytes of many species, but its presence in the mouse has been controversial. Using confocal and electron microscopy, we report that a Balbiani body does arise in mouse neonatal germline cysts and oocytes of primordial follicles but disperses as follicles begin to grow. The mouse Balbiani body contains a core of Golgi elements surrounded by mitochondria and associated endoplasmic reticulum. Because of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
184
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(206 citation statements)
references
References 71 publications
9
184
1
3
Order By: Relevance
“…The study of Cox and Spralding indicates that during Drosophila oogenesis, follicular cells are a source of mitochondria, which enter the oocyte cytoplasm via the ''ring canal'' to form the Balbiani body, thereby supplying virtually all of the mitochondria of the oocyte (Cox and Spradling, 2003;Pepling et al, 2007).…”
Section: Balbiani Bodymentioning
confidence: 99%
“…The study of Cox and Spralding indicates that during Drosophila oogenesis, follicular cells are a source of mitochondria, which enter the oocyte cytoplasm via the ''ring canal'' to form the Balbiani body, thereby supplying virtually all of the mitochondria of the oocyte (Cox and Spradling, 2003;Pepling et al, 2007).…”
Section: Balbiani Bodymentioning
confidence: 99%
“…In Xenopus oocytes, mRNA pulldown experiments have revealed that CPEB-1 specifically interacts with a number of P-body protein components, such as Rck/p54, Pat1, RAP55B, 4E-T, and an EIF4Eb protein (Minshall et al, 2007), and RAP55 was found to be localized to cytoplasmic foci (Tanaka et al, 2006). In the mouse, RAP55, Rck/p54, and CPEB-1 are also expressed in oocytes, but whether these protein indeed interact or form visible P-body-like foci has not been determined (Matsumoto et al, 2005;Racki and Richter, 2006;Pepling et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In Xenopus oocytes, mRNA pulldown experiments have revealed that CPEB-1 specifically interacts with a number of P-body protein components, such as Rck/p54, Pat1, RAP55B, 4E-T, and an EIF4Eb protein (Minshall et al, 2007), and RAP55 was found to be localized to cytoplasmic foci (Tanaka et al, 2006). In the mouse, RAP55, Rck/p54, and CPEB-1 are also expressed in oocytes, but whether these protein indeed interact or form visible P-body-like foci has not been determined (Matsumoto et al, 2005;Racki and Richter, 2006;Pepling et al, 2007).Recently, small noncoding RNAs (miRNAs, endogenous siRNAs, and piRNAs) were also identified in mouse oocytes (Watanabe et al, 2008;Tam et al, 2008). Because the link between P-bodies and RNA interference (RNAi) silencing has been well documented in somatic cells Sen and Blau, 2005;Jakymiw et al, 2005;Liu et al, 2005b), this further suggested that mouse oocytes may also have similar RNA granules.…”
mentioning
confidence: 99%
“…Ironically, the BB was first described in the human oocyte 50 years ago [2], and yet its importance with respect to teasing apart functional relevance during aging in the human ovary was far more recent [3]. And for once, we can safely conclude that something in science (certainly well within the realm of reproductive biology) awaited the rediscovery of the BB in mice [4]. So why the big deal about the BB?…”
mentioning
confidence: 99%